Analisis Tingkat Partisipasi Pemilih Pemula di Universitas Tidar pada Pemilihan Presiden Tahun 2024 - Sahieza, Felisha Nurmalita; AlFaiyad, Muhammad Davieq; Ambarwati, Mutdiyah Retno; Ramadhani, Oktavia; Nugraheni, Carisa Dwi; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2025)
The political participation of first-time voters is a crucial element in the consolidation of democracy in Indonesia, especially in the context of the 2024 General Election. This study aims to analyze the level of participation of first-time voters in the presidential election at Universitas Tidar, identify the influencing factors, and explore effective strategies to enhance it. The research employs a quantitative method using a survey approach with 40 student respondents classified as first-time voters. The findings indicate that participation is influenced by internal factors such as understanding of political issues and political efficacy, as well as external factors like government-led socialization efforts and media influence. Most respondents reported understanding the election procedures and believed that participation in elections represents a civic responsibility. However, challenges remain in increasing participation, particularly in delivering accessible and engaging political information for the younger generation. Strategies to boost participation must consider digital media preferences, engagement with relevant social issues, and the need for continuous political education. The study also highlights the importance of synergy between the government, election organizers, political parties, and civil society organizations in designing innovative, inclusive, and youth-oriented voter engagement programs. These findings are expected to provide practical contributions to improving democratic quality in Indonesia by encouraging the political involvement of younger citizens.